Pengaruh Dana Pihak Ketiga, Capital Adequacy Ratio, Non Performing Loan Dan Tingkat Suku Bunga terhadap Penyaluran Kredit Bank Umum yang Terdaftar di Bursa Efek Indonesia - Venna Melinda; Velicia Velicia; Kenji Lau; Rafida Khairani (Universitas Batanghari Jambi, 2021)
Today's developing economy encourages banks to focus on raising funds and channeling credit to people who need them to meet their needs. The funds he raises are known as DPK. The purpose of this research is to examine and analyze the effect of Third Party Funds, Capital Adequacy Ratio, Non-Performing Loans and Interest Rate Stimulant and Partial on Commercial Bank Credit Distribution listed on the IDX. This type of research used is quantitative. The research is causal and the data is quantitative with a ratio scale. Data collected documentation and secondary data. The total population of commercial banks listed on the IDX in 2014 - 2018 in 45 banks. The research sample consisted of 22 companies. This study was analyzed by multiple linear regression. The result is that Third Party Funds, Non-Performing Loans, Capital Adequacy Ratio, and Partial and stimulant Interest Rates have an influence on Commercial Bank Credit Distribution listed on the IDX.